2020
DOI: 10.3233/wor-203159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stretching on muscle activation in gas cylinder handling

Abstract: BACKGROUND: Previously, a stretching regimen was designed for manual material handling (MMH) of gas cylinders as a potential ergonomic solution for reducing occupational injury. No studies have made use of objective process measures, such as muscle activation levels, for evaluation of effects of stretching programs. OBJECTIVE: Examine acute effects of stretching on muscle activation levels and driver perceived level of exertion in gas cylinder handling during simulated delivery operations. METHODS: A within-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…For instance, an observational rating scale has shown that a stretching routine can reduce the risk of fatigue for certain activities [ 22 ]. Also, muscle fatigue detection during gas cylinder handling tasks was studied via electromyography (EMG) recordings to demonstrate the benefits of including a stretching routine at the beginning of the task execution [ 23 ]. However, this study obtained inconclusive results as (1) the tasks were not long enough to induce muscle fatigue, and (2) they did not provide enough rest to allow muscle recovery between trials with and without a stretching routine [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, an observational rating scale has shown that a stretching routine can reduce the risk of fatigue for certain activities [ 22 ]. Also, muscle fatigue detection during gas cylinder handling tasks was studied via electromyography (EMG) recordings to demonstrate the benefits of including a stretching routine at the beginning of the task execution [ 23 ]. However, this study obtained inconclusive results as (1) the tasks were not long enough to induce muscle fatigue, and (2) they did not provide enough rest to allow muscle recovery between trials with and without a stretching routine [ 23 ].…”
Section: Introductionmentioning
confidence: 99%